THE WORD. ABOUT POETRY OF PROFESSOR HALINA KRUKOWSKA IN THE CONTEXT OF HISTORY OF BIAŁYSTOK CLUB OF CATHOLIC INTELLIGENCE - Кулеша , Даріуш (Кафедра полоністики Навчально-наукового інституту філології Київського національного університету імені Тараса Шевченка, 2022)
The article contains an analysis and interpretation of several poems by professor Halina Krukowska, a literature expert who died in the summer of 2019 and one of those who created the Bialystok Polish Studies. The reading of the poems has been placed in the context of the mysticism of St. John of the Cross and St. Theresa of Jesus. It is accompanied by the history of the Bialystok Club of Catholic Intelligence, whose “Słowo” magazine professor Krukowska edited and published her popular science texts and poems reviewed in the article.

Стаття містить аналіз та інтерпретацію кількох віршів професорки Галіни Круковської, що померла влітку 2019 року, літературознавиці, однієї з творців білостоцької полоністики. Прочитання віршів здійснено у контексті містики св. Яна Хрестителя і св. Терези від Ісуса. Аналіз доповнено історією білостоцького Клубу Католицької Інтелігенції, чий часопис «Слово» редагувала Галіна Круковська, на сторінках якого розміщувала свої популярно-наукові тексти й розглянуті у статті вірші.
СЛОВО. ПРО ВІРШІ ПРОФЕСОРКИ ГАЛІНИ КРУКОВСЬКОЇ В КОНТЕКСТІ ІСТОРІЇ БІЛОСТОЦЬКОГО КЛУБУ КАТОЛИЦЬКОЇ ІНТЕЛІГЕНЦІЇ
Keywords: catholic intelligence; Białystok; history; Halina Krukowska; poetry; поезія; католицька інтелігенція; Білосток; історія; Галіна Круковська